Comparison Of Driving Factors On Impulsive Buying And Purchase Intention : Case Study Of Skincare Products In Tik Tok Live Shopping - Syafika Azizah; Rosa Rilantiana (Amkop Management Accounting Review (AMAR), 2026)
The development of digital technology has driven changes in consumer behavior in online shopping activities, one of which is through the TikTok Live Shopping feature which is widely used in marketing skincare products. This study aims to analyze the influence of Perceived Enjoyment, Perceived Risk, and Scarcity Message on Impulsive Buying and Purchase Intention on TikTok Live Shopping for skincare products in Gresik, with product categories including facial wash, toner, serum, moisturizer, and sunscreen. This study uses a quantitative approach with a causal associative research type. Data collection was carried out through a survey method using a questionnaire distributed online via Google Form to 219 respondents who had participated in TikTok Live Shopping activities for skincare products. Data analysis was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4.0 software. The results showed that Perceived Enjoyment and Scarcity Message had an effect on Impulsive Buying and Purchase Intention, respectively. Meanwhile, Perceived Risk had no effect on Impulsive Buying and Purchase Intention. These findings show that emotional experience factors and scarcity messages have an important role in driving consumer behavior on TikTok Live Shopping skincare products.